Cooperative action of antioxidant defense systems in Drosophila. - Missirlis, F.; Phillips, J.P.; Jackle, H. (Current Biology, 2001)
Molecular oxygen is key to aerobic life but is also converted into cytotoxic byproducts referred to as reactive oxygen species (ROS). Intracellular defense systems that protect cells from ROS-induced damage include glutathione reductase (GR), thioredoxin reductase (TrxR), superoxide dismutase (Sod), and catalase (Cat). Sod and Cat constitute an evolutionary conserved ROS defense system against superoxide; Sod converts superoxide anions to H(2)O(2), and Cat prevents free hydroxyl radical formation by breaking down H(2)O(2) into oxygen and water. As a consequence, they are important effectors in the life span determination of the fly Drosophila. ROS defense by TrxR and GR is more indirect. They transfer reducing equivalents from NADPH to thioredoxin (Trx) and glutathione disulfide (GSSG), respectively, resulting in Trx(SH)(2) and glutathione (GSH), which act as effective intracellular antioxidants. TrxR and GR were found to be molecularly conserved. However, the single GR homolog of Drosophila specifies TrxR activity, which compensates for the absence of a true GR system for recycling GSH. We show that TrxR null mutations reduce the capacity to adequately protect cells from cytotoxic damage, resulting in larval death, whereas mutations causing reduced TrxR activity affect pupal eclosion and cause a severe reduction of the adult life span. We also provide genetic evidence for a functional interaction between TrxR, Sod1, and Cat, indicating that the burden of ROS metabolism in Drosophila is shared by the two defense systems.